Socio-Economic Determinants of Agrarian Succession: A Logistic Regression Analysis of Youth Aspirations in Indonesian Coffee Home Industries - Dwi Valinia Ivanka; Hanifah Yasin (HM Publisher, 2025)
The global coffee supply chain relies heavily on smallholder farmers, yet agrarian communities face a crisis of generational succession. This study investigates the aspirations of rural youth in Pagaralam, South Sumatra, and the socio-economic mechanisms driving their reluctance to inherit family-owned coffee home industries. A cross-sectional quantitative survey was conducted among 200 respondents aged 16–30 from coffee-farming households. To target established enterprises, a purposive sampling strategy was utilized. Data were collected using validated structured questionnaires. A binary logistic regression analysis was employed to identify predictors of generational succession intent. Only 24.5% (n = 49) of respondents expressed a definitive intent to continue the family business, whereas 61.0% (n = 122) preferred urban or digital employment. The predictive model demonstrated a strong fit (Nagelkerke R-squared = 0.428). Significant negative predictors for succession included higher educational attainment (Odds Ratio = 0.30, p-value < 0.001), perceived income volatility (Odds Ratio = 0.32, p-value < 0.01), and the perceived low social status of farming (Odds Ratio = 0.45, p-value < 0.05). Conversely, access to agricultural modernization technology was a strong positive predictor (Odds Ratio = 3.15, p-value < 0.01). In conclusion, youth out-migration from the coffee sector is strongly associated with structural economic barriers and shifting cultural aspirations rather than a lack of foundational knowledge. Securing the future of these industries requires targeted interventions that integrate technological innovation to rebrand coffee processing as a lucrative, high-status entrepreneurial endeavor.